INDIKATOR KINERJA JALAN LONG SEGMENT DI BANTEN DENGAN ANALISIS ANALYTICAL HIERARCHY PROCESS - Ridwan, Novel; Putranto, Leksmono S. (Universitas Tarumanagara, 2020)
The length of National roads in Banten Province along 564 kilometers is spread in several regencies and cities in the Banten region. In managing road implementation, adequate resources are needed so that prompt and appropriate action can be taken to reduce complaints from road users / communities. Implementation of road handling carried out by service providers with a conventional contract system must be done through a procurement process that goes through procedures based on applicable laws and regulations, namely based on Circular Letter of the Director General of Highways No.9 / SE / DB 2015 Implementation of road handling carried out by service providers use the Long Segment System. In the implementation of road handling carried out by service providers with a long segment contract system, service providers must meet the level of road service conditions, so that service providers are able to meet road quality standards. Because road management in Banten Province currently uses the Long Segment System, it is necessary to analyze all aspects of handling the system. This study analyzes these aspects with the AHP (Analytical Hierarchy Process approach based on interviews and questionnaires. Based on the results of the analysis found in long segment work on the highway, the most important aspect to consider is the Drainage Aspect, and the drainage work needs to pay attention to the smooth work all types of channels made in drainage work. sepanjang 564 kilometer tersebar di beberapa kabupaten dan kota di wilayah Banten. Dalam mengelola implementasi jalan, diperlukan sumber daya yang memadai sehingga tindakan yang cepat dan tepat dapat diambil untuk mengurangi keluhan dari pengguna jalan/masyarakat. Implementasi penanganan jalan yang dilakukan oleh penyedia layanan dengan sistem kontrak konvensional harus dilakukan melalui proses pengadaan yang melewati prosedur berdasarkan hukum dan peraturan yang berlaku, yaitu berdasarkan Surat Edaran Direktur Jenderal Bina Marga No.9/SE/DB Tahun 2015 Implementasi penanganan jalan yang dilakukan oleh penyedia layanan menggunakan Sistem Segmen Panjang. Dalam pelaksanaan penanganan jalan yang dilakukan oleh penyedia jasa dengan sistem kontrak segmen panjang, penyedia jasa harus memenuhi tingkat kondisi layanan jalan, ini agar penyedia jasa mampu memenuhi standar kualitas jalan. Karena manajemen jalan di Provinsi Banten saat ini menggunakan Sistem Segmen Panjang, maka perlu analisis segala aspek dalam penanganan sistem tersebut. Penelitian ini menganalisis aspek-aspek ini dengan pendekatan AHP (Analytical Hierarchy Process yang didasarkan dari wawancara dan kuesioner. Berdasarkan hasil analisis ditemukan dalam pekerjaan long segment pada jalan raya, aspek terpenting yang harus diperhatikan adalah Aspek Drainase, dan pada pekerjaan drainase perlu memperhatikan lancaranya pekerjaan semua jenis saluran yang dibuat dalam pekerjaan drainase.